Police-citizen relations across the world: comparing sources and contexts of trust and legitimacy - Oberwittler, Dietrich; Roché, Sebastian (Routledge frontiers of criminal justice, 2018)
Foreword / Michal Tonry -- Introduction -- Towards a broader view of police-citizen relations : how societal cleavages and political contexts shape trust and distrust, legitimacy and illegitimacy / Sebastian Roché and Dietrich Oberwittler -- Police-citizen relations. Multilevel and comparative approaches : neighbourhoods and states -- Recent trends in police-citizen relations and police reform in the United States / Ronald Weitzer -- Ethnicity, group position and police legitimacy : early findings from the European social survey / Ben Bradford, Jonathan Jackson and Mike Hough -- Ethnic disparities in police-initiated controls of adolescents and attitudes towards the police in France and Germany : a tale of four cities / Dietrich Oberwittler and Sebastian Roché -- Police legitimacy and public cooperation : is Japan an outlier in the procedural justice model? / Mai Sato -- Why do Nigerians cooperate with the police? : legitimacy, procedural justice, and other contextual factors in Nigeria / Oluwagbenga Michael Akinlabi -- Societal cleavages and legitimacy : minorities and religions -- Policing marginalized groups in a diverse society : using procedural justice to promote group belongingness and trust in police / Kristina Murphy and Adrian Cherney -- Adolescents' divergent ethnic and religious identities and trust in the police : combining micro- and macro-level determinants in a comparative analysis in France and Germany / Sebastian Roché, Anina Schwarzenbach, Dietrich Oberwittler and Jacques De Maillard -- The impact of the Ferguson, mo police shooting on black and non-black residents' perceptions of police : procedural justice, trust, and legitimacy / Tammy Rinehart Kochel -- Why may police disobey the law? : how divisions in society are a source of the moral right to do bad: the case of Turkey / Sebastian Roché, Mine Özasçilar and Ömer Bilen -- Procedural justice as cause and consequence -- Stop-and-frisk and trust in police in Chicago / Wesley G. Skogan -- Good cops, bad cops : why do police officers treat citizens (dis)respectfully? : findings from Belgium / Maarten Van Craen, Stephan Parmentier and Mina Rauschenbach -- Trust in the finnish police and crime reporting-findings in the context of the Nordic countries / Juha Kääriäinen